The Impact of the COVID-19 Pandemic on the Conduct of Clinical Trials and Potential Ethical Consequences - Jedličková, Anetta (Teorie vědy / Theory of Science, 2023)
The COVID-19 pandemic led to significant changes of the usual procedures in the clinical trials conduct, as well as to modifications of the relevant study documentation, which also affected regular quality assurance activities ensuring the safety of clinical trial participants, compliance with good clinical practice, and the integrity and validity of the clinical trial data collected during the COVID-19 pandemic. The paper deals with the ethical guidelines and legal regulations that govern the conduct of clinical trials and discusses the ethical implications that arose from the forced adjustments of routine processes and procedures in the clinical trial conduct during the COVID-19 public health emergency. The paper also reflects on the ethical consequences of conducting clinical trials during the public health emergency, as well as on means of performing quality assurance activities and a regular oversight of clinical research.